FAKTOR-FAKTOR YANG MEMENGARUHI URGE TO BUY IMPULSIVELY MELALUI ATTITUDE TOWARD INFLUENCER ADS PADA IKLAN LIVE STREAMING INFLUENCER TIKTOK DI JAKARTA - STEVANNY PUTRI SETIAWAN; DENNY SEPTA HARYANTI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2026)
The purpose of this study is to analyze and determine the influence of Influencer Credibility (IC), Celebrity Effect (CE), Perceived Entertainment (PE), Perceived Usefulness (PU), Trust (T), and Attitude toward influencer ads (ATIA) on Urge to Buy Impulsively (UTBI) in TikTok live streaming ads in Jakarta. This study uses a descriptive and causal research design, measuring each variable using a 5-point Likert scale. This study utilized primary and secondary data, and data collection was conducted through a questionnaire. The research sample was obtained through purposive sampling and involved 235 respondents. The method used in this study was Structural Equation Modeling (SEM) with SmartPLS 4.0 and SPSS. The results obtained in this study indicate that the variables IC, CE, PE, PU, T, and ATIA have an influence on the UTBI variable.